2014
DOI: 10.1039/c4ra03508a
|View full text |Cite
|
Sign up to set email alerts
|

Regio- and stereoselective synthesis of novel spiropyrrolidines through 1,3-dipolar cycloaddition reactions of azomethine ylides and 2-styrylquinazolin-4(3H)-ones

Abstract: Efficient regio- and stereoselective synthesis of novel spiropyrrolidines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…The (Z,E)-dipole d 3 then undergoes a 1,3-dipolar cycloaddition reaction with the dipolarophile 1 in a regio-and stereoselective manner (path A). The formation of the exo-regioisomer 5 via path A is more favorable because of the presence of a secondary orbital interaction (SOI) [49,54,55], which occurs between the oxygen atom of the carbonyl of the diketone and the carbon atom of the carbonyl of the dipolarophile as shown in Scheme 4. Conversely, the formation of the other regioisomers or diastereoisomers is less favorable because of steric or electronic repulsion in their corresponding transition states.…”
Section: A Weak Intermolecular N-h••••o Hydrogen Interaction Is Present In the Crystal Structure Of 5m Albeit With Weaker Bonding (D(n••mentioning
confidence: 99%
“…The (Z,E)-dipole d 3 then undergoes a 1,3-dipolar cycloaddition reaction with the dipolarophile 1 in a regio-and stereoselective manner (path A). The formation of the exo-regioisomer 5 via path A is more favorable because of the presence of a secondary orbital interaction (SOI) [49,54,55], which occurs between the oxygen atom of the carbonyl of the diketone and the carbon atom of the carbonyl of the dipolarophile as shown in Scheme 4. Conversely, the formation of the other regioisomers or diastereoisomers is less favorable because of steric or electronic repulsion in their corresponding transition states.…”
Section: A Weak Intermolecular N-h••••o Hydrogen Interaction Is Present In the Crystal Structure Of 5m Albeit With Weaker Bonding (D(n••mentioning
confidence: 99%
“…As was introduced in section , decarboxylation is a relatively mild and powerful strategy for the generation of semistabilized 2-azaallyl anions. Similarly, the tandem iminium condensation/thermal decarboxylation reaction manifold (via carboxylic acids 278 , Scheme ) is a popular method for in situ preparation of N -alkyl azomethine ylides. In 1993, Prato and co-workers demonstrated that C 60 could be converted to the corresponding pyrrolidine by 1,3-dipolar cycloaddition with the N -methyl azomethine ylide generated via thermal decarboxylation of the iminium formed by condensation between sarcosine ( N -methlyglycine) and formaldehyde (Scheme ). This so-called “Prato reaction”, and variations thereof, have since been applied toward the functionalization of fullerenes, graphene and single-walled carbon nanotubes and nanohorns, …”
Section: Azomethine Ylidesmentioning
confidence: 99%
“…Kamal and co‐workers reported an efficient regio‐ and stereoselective synthesis of spiropyrrolidines 329 through the 1,3‐dipolar cycloaddition reaction of 2‐styrylquinazolin‐4(3 H )‐ones 328 with azomethine ylides generated in situ from the decarboxylative coupling of l ‐proline 205 and isatin 307 (Scheme ) . The present approach worked well with a variety of substituted isatins and 2‐styrylquinazolinones.…”
Section: Decarboxylative Reactions Via Azomethine Ylides Pathwaymentioning
confidence: 99%